Respuesta :

9514 1404 393

Answer:

  x = -4

Step-by-step explanation:

The distributive property is used to eliminate parentheses.

  7(x -2) -3(x +3) = 5(x -3) +x . . . . given

  7x -14 -3x -9 = 5x -15 +x . . . . . eliminate parentheses

  4x -23 = 6x -15 . . . . . . . . . . . collect terms

  -8 = 2x . . . . . . . . . . . . . . subtract 4x+15 from both sides

  -4 = x . . . . . . . . . . . . divide by 2

__

Check

  7(-4 -2) -3(-4 +3) = 5(-4 -3) +(-4)

  7(-6) -3(-1) = 5(-7) -4

  -42 +3 = -35 -4

  -39 = -39 . . . . . answer checks OK